(3TYQ GHf GdebQH GdYjhfis - (3Ydj Hf GdebQH Hf efUhQ GdQHYj GdYjhfj, LeGd GdOjf, CHh YHO Gddg,J (B629 (3g` s
(3ChdgG (B:s
( (3gPG eG hLO ef QGFb TYQ Gdedc EHf GdebQH(B) (3CeG MGf ddYVH GdjeGfi Cf jQi HjefGc cGdeNQGb ai ca dGYH s
(3BNQgG (B:s
(3heGYOOJ eTjQkG ef efGbHfG hef HYO KQi HjOjg ehJceG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B245s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B219 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs